Paradise Ridge Winery: Can a Tragedy Strengthen a Brand? - Matthew McDermaid; Sandra K. Newton (Wine Business Journal)
Paradise Ridge Winery had celebrated its grand reopening of its main estate after being destroyed in the 2017 Tubbs wildfire when it was once again forced to close its doors to the COVID-19 pandemic. Rene Byck and his sister, Sonia Byck-Barwick, vice-presidents and co-owners, chose this as a time to completely reevaluate how they were going to interact with the public. They relied so much on tourism and large event hosting that they knew that they needed to capitalize on the potential opportunities present, and also create an effective strategy to navigate the uncertain future of the wine industry. They didn’t know when things might return to normal, so this was the perfect opportunity to become one of the best prepared wineries; but where to focus? Do they consider adjusting the winery’s prices, changing its hospitality operations, and/or investing in further digital and regional advertising? What do they need to account for before they can make any decisions?